2014
DOI: 10.3111/13696998.2014.953679
|View full text |Cite
|
Sign up to set email alerts
|

Costs and utilization of hemophilia A and B patients with and without inhibitors

Abstract: The results suggest that, while the frequency of inhibitors within the hemophilia cohort was low, there was a higher frequency of hospitalizations, and the associated median aggregate costs per year were 3-fold higher than those patients without inhibitors. In contrast, hemophilia B patients experience less severe disease and account for lower aggregate yearly costs compared to either patients with hemophilia A or patients with inhibitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 18 publications
2
34
0
Order By: Relevance
“…For context, a recent health resource utilization analysis of patients with 103 haemophilia reported an average of 6 days of hospital admissions per patient per year and 21 surgical admissions over 2 years (results were not reported by treatment) . Another analysis reported approximately 40% of 155 patients with haemophilia A without inhibitors to have had at least 1 hospitalization over a 5‐year period …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For context, a recent health resource utilization analysis of patients with 103 haemophilia reported an average of 6 days of hospital admissions per patient per year and 21 surgical admissions over 2 years (results were not reported by treatment) . Another analysis reported approximately 40% of 155 patients with haemophilia A without inhibitors to have had at least 1 hospitalization over a 5‐year period …”
Section: Resultsmentioning
confidence: 99%
“…35 Another analysis reported approximately 40% of 155 patients with haemophilia A without inhibitors to have had at least 1 hospitalization over a 5-year period. 36 Annual and total factor VIII consumption was higher in cohorts receiving prophylaxis compared to episodic treatment groups; however, per-infusion FVIII consumption was similar (Table 4). Total FVIII consumption tended to be at least 2 to 4 times higher in prophylaxis compared to episodic treatment groups, with Gringeri and colleagues reporting 8852 vs 3981 units infused per patient per month, respectively, and Ingerslev and colleagues reporting 183 490 vs 39 127 mean annual FVIII use between groups.…”
Section: Economic Outcomesmentioning
confidence: 95%
“…The questionnaire focused on two aspects of transition: talking to the child about health care as an adult and encouraging more independence, and 65% and 81% (respectively) of respondents reported that these had been addressed by their HTC. A similar question asked in a telephone interview in the National Survey of Children with Special Heath Care Needs (parents of children ages [12][13][14][15][16][17] reported that only 40% of the children achieved the transition outcome. While the survey methodology differed from the HTC needs assessment, results suggest that the HTCs may be performing somewhat better than other populations of children with chronic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on bleeding disorder populations have been conducted to evaluate quality of life [11][12][13][14], cost of care [15][16][17][18], attitudes and perceptions [19][20][21][22], and psycho-social issues [23][24][25][26]. In addition, each region has conducted regular patient satisfaction surveys.…”
Section: Introductionmentioning
confidence: 99%
“…Pre-immunisation against the transgene product can occur when the recombinant transgenic protein has been administered. For example, in haemophilia B patients, this can result in the generation of anti-factor IX antibodies when treated by recombinant factor IX (Armstrong et al 2014). Accordingly prior immunisation needs to be carefully considered in clinical trial enrolment criteria.…”
Section: Host Pre-sensitisation or Acquired Immune Responsesmentioning
confidence: 99%